Anatomical and Radiological Description of the Spring Ligament Articular Facet (SLAF). Issue 4 (November 2022) - Kasture, Sarang P.; Mistry, Alpesh; Low, Samantha; Fisher, Andrew; Bond, Alistair P.; Lambert, Laura-Ann; Jayatilaka, Lara; Philpott, Matthew; Fisher, Lauren; Mason, Lyndon W.; Molloy, Andrew P.
Category: Basic Sciences/Biologics; Midfoot/Forefoot Introduction/Purpose: Spring ligament is a principle static stabilizer of the medial longitudinal arch. There is a triangular facet of fibrocartilage in its superomedial bundle that articulates with the talar head which is poorly described in the literature. The aim of this study was to carry out a formal anatomical and radiological description of the spring ligament articular facet (SLAF). Methods: Anatomically, we dissected 10 normally aligned cadaveric lower limbs. The spring ligament was approached from the superior direction. The talus was disarticulated and high-resolution images were taken of the ligament complex. ImageJ and Tracker software was used to calculate the surface area and the maximum linear measurements of the spring ligament articular facet (SLAF). 22 normally aligned feet were analysed on reformatted PD space sequences on MRI using PACS. Results: The meniscus was consistently trapezoid in shape in all specimens. The mean area of the SLAF was 203.31 mm 2 . The average longest proximal to distal length was 11.93 mm and at the shortest plantar and lateral margin was 5.34 mm. The attachment of the SLAF with calcaneum and navicular articular surface was defined by a distinct thick fibrous ligamentous structure that measured 3.67 and 1.69 mm at its medial and lateral margin on the calcaneal side and 2.72 and 2.87 mm respectively on the navicular side. SLAF was visible on MRI but it was not possible to differentiate between SLAF and its investing ligaments. MRI measurements showed a mean surface area of 354 mm 2 with mean thickness of 2.7 - 4.3 mm throughout its course. Conclusion: The paper describes the anatomical and radiological parameters of SLAF, a constant fibrocartilaginous structure within the superomedial portion of the spring ligament, as well as its ligamentous attachments.